Effects of Mulligan Mobilization with Movement in Subacute Lateral Ankle Sprains: A Pragmatic Randomized Trial. (2nd November 2021) - Nguyen, Anh Phong; Pitance, Laurent; Mahaudens, Philippe; Detrembleur, Christine; David, Yuval; Hall, Toby; Hidalgo, Benjamin
ABSTRACT: Objective : In a pragmatic and randomized clinical trial, patients with lateral ankle sprains were assessed, under blinded conditions, for their responsiveness and improvements during Mulligan mobilization-with-movement (MWM) therapy. Methods : Overall, 51 participants with subacute lateral ankle sprains (Grade I–II) were recruited. Following an MWM screening procedure, responders were randomized to either an intervention group (MWM) or a sham group. The MWM group received inferior tibiofibular, talocrural, or cubometatarsal MWM. The treatment or sham was administered upon three sessions, each 4 days apart. Changes from baseline were measured and compared between the sessions for dorsiflexion range of motion, pain, stiffness perception, and the Y-balance test. Results : In total, 43 participants were considered responders to MWM. Using a two-way repeated-measure ANOVA, a statistical and clinically meaningful improvement in dorsiflexion range of motion was revealed in the MWM group (p = 0.004,  1 rst  = +1.762 cm; 3 rd  = +2.714 cm), whereas no improvement following the first session occurred in the sham group (p = 0.454,  1 rst trial = +1.091 cm; 3 rd trial = +1.409 cm). Pain and stiffness significantly improved, yet below the clinically meaningful level. The MWM group demonstrated a significant improvement after three sessions for the Y-balance test (p = 0.001,  +8.857 cm). Conclusion : More than 80% of participants with subacute lateral ankle sprains responded well to the MWM approach. Three sessions of pragmatically determined MWM provided a significant and clinically meaningful benefit in dorsiflexion range of motion and Y-balance test performance compared to a sham treatment.